Quantifying factors limiting soybean yield in Southern Africa: a yield gap decomposition - Omondi, J.O.; Chiduwa, M.S.; Kyei-Boahen, S.; Masikati, P.; Nyagumbo, I. (International Institute of Tropical Agriculture, 2024)
Soybean production in Sub-Saharan Africa (SSA) is increasing as its demand for food, feed, cash, and soil fertility improvement soars. Yet, the difference between the smallholder farmers’ yield and either the attainable in research fields or the potential from crop models is large. Most of the reasons for the yield gap are known including low to non-application of appropriate fertilizers and inoculants, late planting, low plant populations, using recycled seeds, and poor crop management practices. However, quantifying them in terms of yield gap (yield gap decomposition) is a challenge. Here, we assessed the contribution of various crop management practices and inputs to yield gap, the actual potential farmer yield, and the major factors limiting soybean yield increase per unit area. This study showed that to close the soybean yield gap, besides soil nutrients and plant nutrition, soybean variety is the most limiting factor in Malawi and Zambia followed by disease damage in Malawi and seed rate in Zambia. Whereas, in Mozambique, seed rate is significant, although the seeds should have high viability, followed by the variety. Overall, in the Southern Africa region (Malawi, Zambia, and Mozambique) the major soybean yield gap contributors are: variety (63.9%), seed rate (49.7%), and disease damage (36.3%), especially soybean rust, in that order. An indication that through yield gap decomposition, interventions could be prioritized to target the most yield-limiting factors with the minimum resources available to smallholder farmers and immensely narrow the yield gap.